Pyroptosis and Oxidative Stress in Chronic Otitis Media - Müslüm Ayral; İsmail İynen; Servet Erdemes; Osman Erdoğan (The Turkish Journal of Ear Nose and Throat)
Objective: In this study, our aim was to evaluate the relationship between COM, pyroptosis, and oxidative stress.Materials and Methods: This prospective study included 60 patients who underwent surgery for chronic otitis media (COM) and 28 patients as a control group. Pathological tissue was taken from the middle ear in the study group, whereas healthy tissue was taken from the middle ear of patients who underwent cochlear implant surgery and had no signs of infection in the middle ear in the control group. Preoperative serum samples were obtained from all patients. Pyroptosis parameters, Nod-Like Receptor Protein 3 (NLRP3) and Interleukin-1 beta (IL-1β) were investigated. The oxidative stress parameters, including the total antioxidant status (TAS), Total Oxidant Status (TOS), and Oxidative Stress Index (OSI), were also examined.Results: Of the 88 patients included in the study, 52 were men and 36 were women. The patients’ ages ranged from 18 to 59 years, with a mean of 31.07±11.45years. In our study, there was a significant difference in NLRP3, IL-1β, TAS, TOS and OSI values in all case groups compared with the control group in both tissue and serum samples (p<0.001).Conclusion: The significant variation in NLRP3, IL-1β, TAS, TOS and OSI values in tissue and serum compared with the control group indicates that pyroptosis and oxidative stress may play an important role in the presence of COM and cholesteatoma. Understanding the role of pyroptosis in the developmental stages of COM is very important, and elucidation of this relationship may lead to the development of a new treatment method.